Clinical human brucellosis in Malaysia: a case report - Hartady, Tyagita; Saad, Mohd Zamri; Bejo, Siti Khairani; Salisi, Mohd Shahrom (Elsevier, 2014)
Clinical human brucellosis is quite rare in Malaysia although seroconverters are relatively more. This report describes a case of clinical human brucellosis in Malaysia. This case involved a 29-year-old research assistant in a veterinary microbiology laboratory. She complained of intermittent fever, anorexia, profuse sweating, malaise, headache, normotensive (110/60 mm Hg), muscle pain, and arthralgia for 3 d. Blood tests against dengue and malaria were negative thus she was prescribed vitamin C, paracetamol and cough syrup for common flu. The complaints, however, persisted on and off for the next 1 month. She eventually developed anemia and hypotension (90/50 mm Hg) and started to show reduced body weight. Abdominal palpations revealed hepatomegaly and splenomegaly with pain. Thus, brucellosis was suspected before the Rose-Bengal plate test was performed, which revealed the presence of high level of antibody against Brucella. The same test was repeated after 14 d and the results confirmed the presence of high antibody level against Brucella. Following serum agglutination test, a diagnosis of brucellosis was made and she was eventually prescribed rifampicine p.o. once a day combined with doxycycline p.o. twice a day for 6 consecutive weeks before she made a full recovery.